Developing video-conferenced English speaking test (VEST) for classroom-based assessment in tertiary education - David Imamyartha; Mutiara Bilqis; Rizki Febri Andika Hudori; Areta Puspa; Eka Wahjuningsih (Universitas Islam Sultan Agung, 2023)
A proper speaking test may pose challenges to teachers due to suboptimal assessment literacy and the laborious administration of a speaking test. Technology can help alleviate the labor while enabling teachers to ascertain the accuracy and validity of the speaking test. In this direction, this study aims to develop a videoconferenced English-speaking test (henceforth VEST) with the aid of videoconferencing technology. Aligned with the empirics on the use of technology for speaking assessment, this study addresses the gapping void in how videoconferencing technology can be harnessed to escalate the practicality and positive impacts of a classroom-based speaking test in an Indonesian EFL setting. The development adhered to the ADDIE framework involving Analysis, Design, Development, Implementation, and Evaluation. The test prototype was evaluated using a test usefulness analysis framework. The evaluation results were coupled with reflection results of test takers’ experiences to guide test revision. Given the small sample size, this study has unveiled the potential of VEST to improve the praxis of speaking assessment and the resultant test takers’ experience. Implications and recommendations for future studies are also discussed.